Photoelectrochemical High-Value-Added Chemical Production with Improved Selectivity - Li, Yingzhe; Chen, Tao; Chen, Yihuang (Research (Washington), 2024)
Photoelectrochemistry provides an important application in the production of high-value-added chemicals. However, photoelectrochemical organic transformation with high product selectivity remains a challenge. Until now, various technologies have been developed to promote the selectivity of photoelectrochemical high-value-added chemical production. Herein, a novel ion-shielding heterogeneous photoelectrocatalysis strategy for the production of trifluoromethyl group (CF 3 )-containing compounds with high selectivity is described.